Pengaruh Ekstraksi dan Konsentrasi Etanol terhadap Kadar Flavonoid Total dan Aktivitas Antioksidan Ekstrak Jahe Emprit (Zingiber officinale var. Amarum): Effect of Ethanol Extraction and Concentration on Total Flavonoid Content and Antioxidant Activity of Emprit Ginger Extract (Zingiber officinale var. Amarum) - Avian Tri Wahyudi; Tri Minarsih (Indonesian Journal of Pharmacy and Natural Product, 2023)
Ginger emprit or Zingiber officinale var. Amarum contains flavonoids which have pharmacological activities such as antioxidants. Extraction of metabolites through a method using a solvent affects the levels of compounds and the level of pharmacological activity. The purpose of this study was to analyze the effect of different maceration treatments and ethanol concentrations on total flavonoid levels and antioxidant activity of Emprit Ginger extract. The research method in this test begins with collecting samples of Ginger Emprit obtained from Temanggung. Extraction was carried out by maceration and remaceration methods. Determination of total flavonoid content using UV-Vis spectrophotometric method. Testing of antioxidant activity using the DPPH method, absorbance was measured using UV-Vis Spectrophotometry. This test resulted in total flavonoid content of Ginger Emprit extract: maceration-ethanol 70%: 0,674 mgQE/g, remaceration-ethanol 70%: 0,659 mgQE/g, maceration-ethanol 96%: 0,601 mgQE/g, remaceration-ethanol 96%: 0,643 mgQE /g. The results of the determination of the antioxidant activity of the sample with parameter IC50 value for each treatment, on the maceration-ethanol 70% method: 56,58 ppm; remaceration-ethanol70%: 22,1 ppm ; maceration-ethanol 96%: 87,7 ppm; remaceration-ethanol 96%: 67,42 ppm. Based on these results, the Independent-Samples Kruskal-Wallis Test Summary statistical test with variations in extraction methods and solvents did not provide a significant difference in total flavonoid levels with a sig value of 0.447 > 0.05, but resulted in significant differences in the antioxidant activity of emprit ginger extract with a value sig of <0.05 ABSTRAK Jahe emprit Zingiber officinale var. Amarum mengandung flavonoid yang memiliki aktivitas farmakologis diantaranya sebagai antioksidan. Penyarian metabolit melalui suatu metode dengan menggunakan pelarut mempengaruhi kadar senyawa dan tingkat aktivitas farmakologisnya. Tujuan penelitian ini adalah untuk menganalisi pengaruh perbedaan perlakuan proses maserasi dan konsentrasi etanol terhadap kadar flavonoid total dan aktivitas antioksidan ekstrak Jahe Emprit. Metode penelitan pada pengujian ini diawali dengan pengumpulan sampel Jahe Emprit diperoleh dari Temanggung. Ekstraksi dilakukan dengan metode maserasi dan remaserasi. Penetapan kadar flavonoid total menggunakan metode spektrofotometri UV-Vis. Pengujian aktivitas antioksidan menggunakan metode DPPH, diukur absorbansi menggunakan Spektrofotometri UV-Vis. kadar flavonoid total ekstrak Jahe Emprit denganmetode maserasi (etanol 70%) 0,674 mgQE/g , remaserasi (etanol 70%) 0,659 mgQE/g, maserasi (etanol 96%) 0,601 mgQE/g, dan remaserasi (etanol 96%) 0,643 mgQE/g. nilai IC50 sampeldiperoleh hasil pada metode maserasi (etanol 70%) sebesar 56,58ppm); remaserasi (etanol 70%) 22,1 ppm ; maserasi (etanol 96%) 87,7 ppm; dan remaserasi (etanol 96%) sebesar 67,42 ppm. Berdasarkan hasil tersebut, dilakukan uji statistik Independent-Samples Kruskal-Wallis Test Summary variasi metode ekstraksi dan pelarut tidak memberikan perbedaan signifikan pada kadar flavonoid total dengan nilai sig sebesar 0,447 > 0,05, namun menghasilkan perbedaan signifikan pada aktivitas antioksidan ekstrak jahe emprit dengan nilai sig sebesar < 0,05